The Relationship Between Fear of COVID-19 and Online Aggressive Behavior: A Moderated Mediation Model - Ye, Baojuan; Zeng, Yadi; Im, Hohjin; Liu, Mingfan; Wang, Xinqiang; Yang, Qiang (Frontiers in Psychology, 2021)
Amid the COVID-19 pandemic, fear has run rampant across the globe. To curb the spread of the virus, several governments have taken measures to drastically transition businesses, work, and schooling to virtual settings. While such transitions are warranted and well-intended, these measures may come with unforeseen consequences. Namely, one’s fear of COVID-19 may more readily manifest as aggressive behaviors in an otherwise incognito virtual social ecology. In the current research, a moderated mediation model examined the mechanisms underlying the relation between fear of COVID-19 and overt and relational aggressive online behavior among Chinese college students. Utilizing a large sample of Chinese college students (N = 2,799), results indicated that moral disengagement mediated the effect of fear of COVID-19 on college students’ overt and relational online aggressive behavior. A positive family cohesion buffered the effect of moral disengagement on relational aggressive behavior, but only for females. The findings, theoretical contributions, and practical implications of the present paper are also discussed.